DEVELOPING TEACHING MATERIALS BASED ON CONFIDENCE CHARACTER EDUCATION TO IMPROVE STUDENTS’ READING SKILLS AT GRADE IV ELEMENTARY SCHOOLS - Silvia Indriani; Sri Utaminingsih; Mohammad Kanzunnudin (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to describe the need for developing teaching materials based on confident character education, to describe the product design of teaching materials development, and to explain the acceptability of developing teaching materials based on confident character education in order to improve studennts’ reading skills at grade IV. This study was conducted at three elementary schools in Kecamatan Kaliwungu Kudus in November 2020. Teaching materials referred to a set of learning materials/substances (teaching materials) arranged systematically, presenting a complete figure of the competencies that students should master in learning activities. According to Lauster in Ghufron (2011: 36), the aspects contained in self-confidence included: self-belief, optimism, positive attitude, objective, responsible, and rational. Research and development (R & D) method was utilized to develop or validate the products used in education and learning. This teaching material was effective in improving students' reading aloud skills. This was evidenced from the results of the increase in the n-gain index in the experimental class which was higher than the control class. The experimental class experienced an increase in gain of 0.57 in the medium category and the control class by 0.25 in the low category